1992
DOI: 10.1055/s-2007-1023758
|View full text |Cite
|
Sign up to set email alerts
|

Ein neues Verfahren zur kontinuierlichen Messung der fetalen Sauerstoffsättigung sub partu

Abstract: The principal aim of foetal monitoring during labor is early detection of hypoxia. Current methods are unable to accomplish this task. Pulse oximetry permits continuous measurement of oxygen saturation and is the best method to detect early hypoxia. In this report, an optical scalp electrode is presented, which permits continuous monitoring of foetal oxygen saturation during labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…The benefit of CTG during delivery is under discussion; 2 however, currently, the British, Americans and Germans advise the use of CTGs. Critics emphasise the high inter‐ and intra‐observer variability of manual CTG evaluation 16–23 . Various score systems have been developed, 24 but only the FIGO classification has been accepted after Spencer et al 13 showed a correlation of this classification system with fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of CTG during delivery is under discussion; 2 however, currently, the British, Americans and Germans advise the use of CTGs. Critics emphasise the high inter‐ and intra‐observer variability of manual CTG evaluation 16–23 . Various score systems have been developed, 24 but only the FIGO classification has been accepted after Spencer et al 13 showed a correlation of this classification system with fetal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that simultaneous registration of fetal arterial oxygen saturation and fetal heart rate -Oxycardiotocography (OCTG) -could be a precise and effective way to detect inadequate fetal oxygen supply [1].…”
Section: Methods and Technologymentioning
confidence: 99%
“…Die Patientin ist bei dieser Überwachung an das Kreißbett gebunden und kann nicht mobilisiert werden. Knitza et al [5] haben einen Sensor entwickelt, der in eine ᭤ CTG-Kopfelektrode integriert wurde und neben der direkten FHF-Ableitung auch den Verlauf der Sauerstoffsättigung anzeigt. Dieses Verfahren hat den Vorteil, daß es weniger Störungen bei der Ableitung der Signale verursacht.…”
Section: Pulsoxymetrie 2 Systemeunclassified